Investigation of the combined influence of temperature and humidity on fatigue crack growth rate in Al6082 alloy in a coastal environment - Alqahatni, Ibrahim; Starr, Andrew; Khan, Muhammad (MDPI, 2023)
The fatigue crack growth rate (FCGR) of aluminium alloys under the combined influence of temperature and humidity remains a relatively unexplored area, receiving limited attention due to its intricate nature and challenges in predicting the combined impact of these factors. The challenge was to investigate and address the specific mechanisms and interactions between temperature and humidity, as in coastal environment conditions, on the FCGR of aluminium alloy. The present study conducts a comprehensive investigation into the combined influence of temperature and humidity on the FCGR of the Al6082 alloy. The fatigue pre-cracked compact tension specimens were corroded for 7 days and then subjected to various temperature and humidity conditions in a thermal chamber for 3 days to simulate coastal environments. The obtained data were analysed to determine the influence of temperature and humidity on the FCGR of the Al6082 alloy. An empirical model was also established to precisely predict fatigue life cycle values under these environmental conditions. The correlation between FCGR and fracture toughness models was also examined. The Al6082 alloy exhibits a 34% increase in the Paris constant C, indicating reduced FCGR resistance due to elevated temperature and humidity levels. At the same time, fatigue, corrosion, moisture-assisted crack propagation, and hydrogen embrittlement lead to a 27% decrease in threshold fracture toughness. The developed model exhibited accurate predictions for fatigue life cycles, and the correlation between fracture toughness and FCGR showed an error of less than 10%, indicating a strong relationship between these parameters.
Keywords: Al-Mg-Mn-Si alloy; fracture toughness; coastal environments; polynomial model; failure mechanism